2019
DOI: 10.1103/physreve.99.042902
|View full text |Cite
|
Sign up to set email alerts
|

Drastic slowdown of the Rayleigh-like wave in unjammed granular suspensions

Abstract: We present an experimental investigation of shear elastic wave propagation along the surface of a dense granular suspension. Using an ultrafast ultrasound scanner, we monitor the softening of the shear wave velocity inside the optically opaque medium as the driving amplitude increases. For such nonlinear behavior two regimes are found: in the first regime, we observe a significant shear modulus weakening, but without visible grain rearrangements.In the second regime, there is a clear grain rearrangement accomp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Then, the weakening of the granular material is presumably ascribed to the modification of the contact network by the acoustic vibration. Indeed, it has been shown that the coefficient of friction between two smooth solid spheres can be reduced via a mechanism of acoustic lubrication 34 , leading to the softening of the tangential contact stiffness and accordingly to a decrease of the sound velocities observed in granular packings 24,30,31 . To rationalize this hypothesis in disordered granular packing, we rely on a friction model developed for a multi-contact solid interface in which the shear interfacial stiffness is reduced through the slipping of asperities under oscillatory shear 33 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, the weakening of the granular material is presumably ascribed to the modification of the contact network by the acoustic vibration. Indeed, it has been shown that the coefficient of friction between two smooth solid spheres can be reduced via a mechanism of acoustic lubrication 34 , leading to the softening of the tangential contact stiffness and accordingly to a decrease of the sound velocities observed in granular packings 24,30,31 . To rationalize this hypothesis in disordered granular packing, we rely on a friction model developed for a multi-contact solid interface in which the shear interfacial stiffness is reduced through the slipping of asperities under oscillatory shear 33 .…”
Section: Discussionmentioning
confidence: 99%
“…To rationalize this hypothesis in disordered granular packing, we rely on a friction model developed for a multi-contact solid interface in which the shear interfacial stiffness is reduced through the slipping of asperities under oscillatory shear 33 . If we generalize this concept by replacing the asperities by the grain contacts, we can explain the softening of the shear modulus G and thus of wave velocity observed in a 3D dense granular suspension 31 via the slipping of the contacts without any rearrangement of grains. As the yield stress τ 0 (as well as µ 0 = τ 0 /P g ) is roughly proportional to the shear modulus (µ 0 ~ G) in a yield stress fluid 3,27 , we may adopt the formula developed for the shear modulus softening as 31,33 , µ 0 / µ 0 * ~ G/ G 0 ≈ 1/[1+Γ/ (2µ p ))+(5/4)(Γ/ (2µ p )) 2 ] induced by the external vibration Γ (<1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In dense suspensions where solids are in cohesionless contact, the bulk and rigidity moduli also depend on the confining pressure and amplitude of the perturbation, which affects the non-affine motions of the grains, contact slidings, and shear dilatancy (e.g. Makse et al 2004, Brum et al 2019. Such phenomena may induce either strengthening or weakening of the rigidity of the suspension because of the change in the contact network (Van den Wildenberg et al 2013).…”
Section: Iv2 Limit Of Validity Of the Modelmentioning
confidence: 99%